1997
DOI: 10.1046/j.1464-410x.1997.26511.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations in the tunica albuginea of the penis: impact of Peyronie's disease, ageing and impotence

Abstract: Objective  To investigate whether changes in the structure of the tunica albuginea influence the development of erectile dysfunction. Patients and methods  Biopsy specimens taken from the tunica of 64 patients (both potent and impotent) with and without Peyronie's disease were evaluated. Tissue samples were stained and examined under light and electron microscopy, and the concentration of elastic fibres present in each was measured using computerized image analysis. Results  The concentration of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
1
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 8 publications
4
82
1
8
Order By: Relevance
“…For example, in aged rats, degenerative changes have been observed in elastic fibers of the TA, and these could be associated with the lower intracavernosal pressures also found in these aged animals 22 . In humans, the concentration of elastic fibers in the TA decreases with age 18 , which is consistent with a reduction in the extensibility 33 and elasticity 34 of the penis in aged individuals. Although a direct causative role for elastic fibers in erectile dysfunction cannot be established yet, it has been shown nonetheless that their content is decreased in the TA from impotent men 15 , 18 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…For example, in aged rats, degenerative changes have been observed in elastic fibers of the TA, and these could be associated with the lower intracavernosal pressures also found in these aged animals 22 . In humans, the concentration of elastic fibers in the TA decreases with age 18 , which is consistent with a reduction in the extensibility 33 and elasticity 34 of the penis in aged individuals. Although a direct causative role for elastic fibers in erectile dysfunction cannot be established yet, it has been shown nonetheless that their content is decreased in the TA from impotent men 15 , 18 .…”
Section: Discussionsupporting
confidence: 65%
“…In view of the involvement of elastic fibers in penile function and disorders, such data would provide important information on the rabbit reproductive biology and extend the applicability of the penis of this animal as an experimental model. For example, in humans, elastic fibers are altered in different types of erectile dysfunction 18,19 and their content is reduced in the TA of elderly individuals 18 , while similar, age-related data exist for erectile tissues of the rat penis [20][21][22] . It should be noted also that correlations between extracellular matrix composition and age are particularly relevant in short-lived animals such as the rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…In this classi®cation, we did not take the plaque size into consideration since recent studies have shown that the tunica albuginea is effected as a whole in Peyronie's disease. 7,13,26 Sexual dysfunction is reported to be a part of presenting symptom complexes in 4 to 80% of Peyronie's patients in previously published series. 12,15 Although excessive angulation due to penile curvature, pain on erection, tenderness of the plaque and performance anxiety may all contribute to ED, it has been shown that penile vascular abnormalities are responsible for ED in 61 ± 70% of cases.…”
Section: Discussionmentioning
confidence: 95%
“…Microscopically, the tunica albuginea is largely composed by fibrillar collagen type I, woven with elastin fibers, in order to form organized structures (5). Even the plaques of PD are mostly constituted from collagen type I and III (6), but the elastin component, which gives to the tunica albuginea elongation properties up to 150%, is altered: the decrease elastin, as well the alterations in the arrangement of the tunic layers, are characteristics of PD, that can lead to deviations in penile erection and erectile dysfunction (7). More recent papers have identified a strong association of PD with both Dupuytren's disease and the HLA B-27 (8).…”
Section: Discussionmentioning
confidence: 99%